Law of torts - Gandhi, B M (Lucknow, 2014)
The present fourth edition of this popular volume is a simple and lucid presentation of various topics on the tort law that fall under General Principles, Specific Torts, Statutory Compensation and the Consumer Protection Act, 1986.
Keywords: Law- Torts